Circumstantial Evidence in The Indonesian Criminal Justice System Perspective of Substantive Justice and The Principle of Restorative Justice (Contrarius Series: Law & Social Justice, 2026)
This study examines the role and application of circumstantial evidence in Indonesia’s criminal justice system and its alignment with restorative justice principles. Using a normative juridical approach with statutory, comparative, and conceptual methods, the research reveals that circumstantial evidence plays a vital role when direct proof is unavailable. However, its application often challenges substantive and restorative justice due to potential bias and unclear legal guidelines. The study highlights, first the critical importance of applying circumstantial evidence within Indonesia’s criminal justice system as a form of indicatory evidence that can strengthen law enforcement. Although circumstantial evidence holds significant potential in supporting the proof of criminal cases, its application must be conducted with utmost caution to ensure that the principles of restorative justice are upheld. The analysis demonstrates that, when applied correctly, circumstantial evidence can make a substantial contribution to achieving substantive justice, provided that evidentiary standards are reinforced, and its use is supported by other evidence that is causally linked and relevant to the offense in question. Second, the application of circumstantial evidence requires careful consideration due to the risks of bias and injustice, which may undermine the integrity of the judicial process. Aligning Indonesia’s criminal justice system more closely with restorative justice principles allows the system not only to focus on punishment but also on restoration and rehabilitation for all parties involved. While circumstantial evidence plays a pivotal role in proving criminal cases, its success in achieving substantive justice depends on prudent, careful, and principled application consistent with the core tenets of restorative justice.